2006
DOI: 10.1104/pp.106.079202
|View full text |Cite
|
Sign up to set email alerts
|

Differential Roles of Arabidopsis Heterotrimeric G-Protein Subunits in Modulating Cell Division in Roots

Abstract: Signaling through heterotrimeric G proteins is conserved in diverse eukaryotes. Compared to vertebrates, the simpler repertoire of G-protein complex and accessory components in Arabidopsis (Arabidopsis thaliana) offers a unique advantage over all other multicellular, genetic-model systems for dissecting the mechanism of G-protein signal transduction. One of several biological processes that the G-protein complex regulates in Arabidopsis is cell division. We determined cell production rate in the primary root a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
163
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(177 citation statements)
references
References 59 publications
10
163
2
1
Order By: Relevance
“…Association of the AGB1-GFP fusion with the plasma membrane is consistent with evidence that AGB1 is a peripheral, membrane-associated protein (Obrdlik et al 2000), and recent localization data using a yellow fluorescent protein-AGB1 fusion (Chen et al 2006a). Node-like structures in the plasma membrane similar to those formed by the AGB1-GFP fusion have been observed for GFP-tagged GCR1 (Humphrey and Botella 2001), and may represent caveolae, specialized plasma membrane structures that are highly enriched in signalling proteins including G-proteins and GPCRs (White and Anderson 2005).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Association of the AGB1-GFP fusion with the plasma membrane is consistent with evidence that AGB1 is a peripheral, membrane-associated protein (Obrdlik et al 2000), and recent localization data using a yellow fluorescent protein-AGB1 fusion (Chen et al 2006a). Node-like structures in the plasma membrane similar to those formed by the AGB1-GFP fusion have been observed for GFP-tagged GCR1 (Humphrey and Botella 2001), and may represent caveolae, specialized plasma membrane structures that are highly enriched in signalling proteins including G-proteins and GPCRs (White and Anderson 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Another recurring feature of plant G-proteins is expression in meristematic regions, previously attributed to a role in regulation of cell division (Weiss et al 1993;Huang et al 1994) and since confirmed for both GPA1 and AGB1 (Ullah et al , 2003. Recently, a study using knockout mutants suggested different roles for Ga and Gbc in the regulation of cell proliferation in roots (Chen et al 2006a). In the root apical meristem, it was found that Ga is a positive modulator of cell division, while the Gbc dimer acts as a negative modulator by sequestering Ga in the heterotrimer complex.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Because growth phenotypes may vary with subtle differences in environmental conditions Pandey et al, 2006), gpa1-3, agb1-2, gpa1-4 agb1-2 double mutant and the xlg triple mutant were grown and assessed simultaneously for growth assays, even for established gpa1 and agb1 phenotypes. When grown in darkness under our particular conditions, plants harboring an agb1 mutation also had longer roots than wild type (as reported in lightgrown plants; Chen et al, 2006), although not as long as the xlg triple mutant ( Figure S6a). Root length of the gpa1-3 mutant was indistinguishable from wild type, as has also been previously reported for light-grown plants Pandey et al, 2006;Ullah et al, 2003).…”
Section: Comparison Of Xlgs and Heterotrimeric G Proteinsmentioning
confidence: 73%
“…11,12) Previous studies have shown that the A. thaliana heterotrimeric G protein is involved in stress responses as well as in development. [13][14][15][16][17][18][19][20][21] Although many flg22-and elf18-induced responses have been studied, the components linking PAMP perception with early signaling events are still unknown. Here we show that in agb1-2 (AGB1 null mutation) mutants, ROS production triggered by flg22 or elf18 is significantly reduced and elf18-stimulated PTI against Agrobacterium tumefaciens is impaired.…”
mentioning
confidence: 99%